Analysis of an indirect air heater solar dryer with multiple PCM. (2016) - Sreerag, T.S.; Jithish, K.S.
This paper deals with designing an experimental model of an indirect solar dryer which uses phase change materials (PCMs) for thermal energy storage. Corrugated aluminium sheet is used as the absorber plate. Aluminium pipes of 3/4" OD are welded under the corrugated sheet to store the PCM. Here, multiple PCMs are used, one with a high melting point and the other one with a lower melting point for the purpose of improving efficiency. A single air pass model in which air moves over the absorber plate is fixed for the study. Air is heated in air heater section which also contains thermal energy storage. Part of the energy obtained in the air heater section is first used to heat and melt the PCM. This heat energy is stored in the PCM and remaining energy in the heated air moves to drying chamber in which the drying process takes place. When the sun's insolation reduces, discharging from the PCM take place. Thus, it reduces the fluctuation in the energy and thus provides a more continuous energy to the system. Glass wool is used as the insulation material. Different parameters for this air heater-dryer have been calculated.